Ensamkommande : En kvalitativ studie om ensamkommande barns/ungdomars etablering i samhället - Henell, Julia (2013)
The numbers of unaccompanied children / young people who comes to Sweden to seek asylum has markedly increased. Migration Board forecasts point not either on that the growth will halt. When the unaccompanied children comes to Sweden they often have separate traumatic events in their luggage but previous studies from children in conflict countries shows that there are conditions in the destination country that will affect them in the long run. Therefore, a good establishment in the society of great significance for the unaccompanied children / young people's future. The purpose of this study was to investigate the factors that may be contributing to a positive presence in the community. The study is based on two focus where one is on the staff at shelters for unaccompanied children / young people working with children / young people's presence in the community. The second is directed against the unaccompanied children / young people's own experiences of meeting with Swedish society, based on the capabilities and limitations of their establishment. Interviews were conducted with staff working on hvb - lodging for unaccompanied children / young people and the children / young people living on the premises. Currently 13 of 14 municipalities in Norrbotten accept unaccompanied children / adolescents. Of the 13 municipalities which currently conducts accommodations for unaccompanied children / adolescents were Boden, Kiruna, Övertorneå and Arjeplog. Municipalities were selected by its regional spread to thus create a relatively reliable and presentable picture of Norrbotten. Results are based partly on the interviews but also from the relevant literature. In the interviews with young people reveals that they are relatively satisfied and happy with their lives in Sweden. Most of them have an active outdoor life and lots of friends. It was stated, however, that it lacked venues where people could meet and connect with Swedish adolescents as school situation was perceived as very segregated. To get in touch with Swedish ...